A Member of Complementary Medicinal Food: Anatolian Royal Jellies, Their Chemical Compositions, and Antioxidant Properties. (October 2016) - Kolayli, Sevgi; Sahin, Huseyin; Can, Zehra; Yildiz, Oktay; Malkoc, Meltem; Asadov, Alsever
This study investigated various chemical and antioxidant properties of Anatolian royal jelly samples. Moisture, pH, total protein, 10-hydroxy-2-decenoic acid (10-HDA) and sugars were analyzed from 18 samples. Total phenolic contents, ferric reducing antioxidant capacity and 2, 2-diphenyl-1-picryhydrazyl (DPPH) free radical scavenging activity were measured as antioxidant determinants. 10-HDA contents and total protein content of fresh weight ranged between 1.0% and 3.9%, and 11.4% and 15.8%, respectively. The main sugars detected were glucose and fructose. Maltose, trehalose, and melibiose were detected at less than 1.0% in all samples. Lactose, a milk sugar, was detected in only 3 samples, at values between 0.8% and 1.4%. Total henolic content ranged from 91.0 to 301.0 mg gallic acid equivalents/kg fresh weight. Antioxidant activity is due to both to the total phenolic content, proteins and fatty acids of royal jelly. Anatolian royal jelly samples were not different from other royal jelly samples from across the world.